Influência da aterosclerose no desenvolvimento da periodontite apical: estudo histológico em ratos - Fernandes, Juliana Nobre Navarro [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Previous studies have demonstrated that endodontic infection exerts effects on systemic health, as well as certain alterations systems, are able to modulate the development of endodontic infection. The objective of this work was to evaluate the effect of atherosclerosis on the development of endodontic infection in an animal model. Wistar rats were divided into 4 groups with 10 animals each: control rats (C); rats with endodontic infection (IE); rats with atherosclerosis (AT); rats with AT and IE (AT+IE). AT was induced by means of a tie made around the carotid artery associated with an overdose of vitamin D3 (45,000 IU / drop or 1,125,000 IU / ml) and a hyperlipidic diet. After 30 days of AT induction, an IE was induced by exposing the pulp of the upper and lower first and second molars to the oral environment. After another 30 days, the rats were killed, the mandibles were removed and laboratory processed for light microscopy and histological and histometric analyzes of apical periodontitis. The results were evaluated by statistical tests (p <0.05). Simulation of the intensity of the inflammatory infiltrate between the IE and AT + IE groups (p> 0.05) could be observed, however, a higher bone loss was observed in the periapical region in the IE+AT group, when compared to the IE group. It may be concluded that atherosclerosis when associated with the presence of multiple foci of endodontic infection and capable of significantly exacerbating the loss of periapical bone structure in Wistar rats

Estudos prévios demonstraram que a infecção endodôntica exerce efeitos sobre a saúde sistêmica, bem como certas alterações sistêmicas são capazes de modular o desenvolvimento da infecção endodôntica. O objetivo deste trabalho foi avaliar o efeito da aterosclerose no desenvolvimento da infecção endodôntica em modelo animal. Foram utilizados 40 ratos Wistar divididos em 4 grupos com 10 animais cada: ratos controle (C); ratos com infecção endodôntica (IE); ratos com aterosclerose (AT); ratos com AT e IE (AT+IE). A AT foi induzida por meio de uma amarria realizada em torno da artéria carótida associada a uma superdose de vitamina D3 (45.000 UI/ gota ou 1.125.000 UI/ml) e dieta hiperlipídica. Após 30 dias da indução da AT, a IE foi induzida por meio da exposição da polpa dos primeiros e segundos molares superiores e inferiores ao meio oral. Decorridos mais 30 dias, os ratos foram mortos, as mandíbulas foram removidas e processadas laboratorialmente para avaliação em microscopia de luz e análises histológica e histométrica da periodontite apical. Os resultados foram analisados por testes estatísticos (p<0,05). Pode-se observar semelhança na intensidade do infiltrado inflamatório entre os grupos IE e AT+IE (p>0,05), no entanto observou-se maior perda óssea na região periapical no grupo IE+AT, quando comparado ao grupo IE. Conclui-se que a aterosclerose quando associada a presença de múltiplos focos de infecção endodôntica é capaz de exacerbar significativamente a perda de estrutura óssea periapical em ratos Wistar
Keywords: Aterosclerose; Periodontite periapical; Endodontia; Ratos Wistar; Atherosclerosis